Kondisi Mental Pemain Tim Bolabasket Putra SMP Muhammadiyah 12 Sebelum Bertanding di Kejuaran DBL - Raditya Dian P, ; Himawan Wismanadi, (Kepelatihan Olahraga, 2010)
Healthy in wide meaning include  physical healthy situation, bounces and social and not merely situation of free of disease or weakness. In the implicit understanding is  a situation showing level of human body functional ability . General Athletic activity / physical practice can increase degree of health, either corporeal fitness and also mental health. Basketball game is not even relies on technique element, just tactics and also physical but also psychology aspect plays a part is significant important enough, because in achievement athletics, the role of athletics psychology very dominant to  jacking up the athlete achievement. This research aim is to know the bouncing condition of SMP Muhammadiyah male basketball team player before contesting in championship of detection basketball league. Method applied in this research is descriptive quantitative, because research result is presented in the descriptive form by using statistic numbers. Populations in this research are extra school male students, which amounts 30 students. While taken 14 student by porposive sample. Analysis applied is descriptive analysis data with simple statistic analysis where descriptive analysis data that is depicting situation or phenomenon status. Data which collected is data having the character of quantitative that is formulated with calculation statistic. To look for value condition overall of bouncing male basketball team player of SMP Muhammadiyah after contesting in championship of DBL applies formula , M = mean / averages, M = , M = mean / averages, Σx = number of values, N = individuals number . Based on research result from seven of instrument which has been checked with simple statistic that is with looking for mean, feeling ready can be formulated that instrument, energy and full of energy and self assessment (PES = match I = 3,084; match II = 2,868; match II = 2,8), (PDR = match I = 3; match II = 2,732; match III = 2,532) influential enough in third contest at bouncing condition male basket football player of SMP Muhammadiyah 12 before contesting in championship of detection Basketball league. Visible that instrument fatigue (KLH = match I = 1,084; match II = 0,9; match III = 0,568), angry situation (AMR = match I = 2,168; match II = 1,45; match III = 1), stress (KTG = match I = 2,368; match II = 1,516; match III = 1,468), situation confuses (SSB = match I = 1,732; match II = 1,25; match III = 1,034), depression (DPS = match I = 0,832; match II = 0,932; match III = 0,652), unable to have an influence with the condition of bouncing male basket football player of SMP Muhammadiyah 12 before contesting in championship of Detection Basketball League